Nature, Content and Methods of Moralizing in the Pedagogical System of I. Kant - Šileikaitė, Diana (Acta Paedagogica Vilnensia, 2003)
The present article has the objective to represent the conception of moral education of the famous German philosopher of the 18th century Immanuel Kant (1724-1804) by means of hermeneutic understanding and interpretation of Kant's texts and theoretical analysis of data supplied by relevant literature material as well as more systematic analysis of the thus identified research results. In the article an attempt is made to analyse Kant’s conception of moral education in the overall context of his critical and practical philosophy and his pedagogical system. The presentation of Kant’s conception of moral education is primarily due to the nature of moralization, his position compared to discipline, culture and civilization, the content and the received method of moralization. Moreover, the timeliness of the Kantian conception as well as its importance for the moral education in the present is pointed.
Keywords: practical philosophy; pedagogical system; moral education; methods of moralization; I. Kant